Managerial ownership and CSR disclosure in achieving SDGS: Evidence from IDX-Listed mining firms (2018-2023) - Saleha, Intan Putri; Siregar, Johannes Kristian (Junal Ilmu Manajemen, 2025)
This study examines how management ownership affects corporate social responsibility (CSR) in mining businesses that are listed between 2018 and 2023 on the Indonesia Stock Exchange (IDX). The findings indicate that the level of managerial ownership disclosure tends to experience fluctuating declines, while CSR disclosure in mining sector companies remains relatively strong. The population of this study consists of 59 mining sector companies. Secondary data in the form of financial reports were obtained from the official IDX website (www.idx.co.id). A total of 10 companies were selected as samples using a non-probability sampling method with purposive sampling technique. The results of this study indicate that managerial ownership has a significant partial influence on corporate social responsibility in mining sector companies listed on the Indonesia Stock Exchange during the study period.